Saving the life of a national sport organization with strategy and governance - Parent, Milena M. (London : Human Kinetics, Inc, 2022)
Endurance Canada is facing a dire situation. It must turn itself around or face bankruptcy. The problems are piling up for Endurance Canada's Board of Directors. Over the last 20 years, the Board's Chair, Bill Fitzpatrick, has seen his sports athletes go from winning Olympic medals to not having any medals internationally. Within Endurance Canada, he has seen high staff turnover and burnout, power struggles between the national and provincial/territorial levels, and their revenues have been hit hard. COVID-19 was the proverbial nail in the coffin. Something drastic needs to happen. So, Bill brings in Amanda Tsang, a strategy expert. She has 1 month to come up with a plan to bring Endurance Canada back to life. The case follows Amanda as she reviews the strategy, structure, and governance issues in the organization. This fictional case asks students to (a) develop a strategic plan for Endurance Canada, (b) show how structure and strategy are interrelated, and (c) reflect on governance issues in a multilevel governance system.strategic planning, structure, design archetypes, sport system, capacity.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Organizational behavior -- Canada; Strategic planning -- Canada -- Case studies